Statistical and lacunary statistical convergence of interval numbers in topological groups - Esi, Ayhan (Acta Scientiarum. Technology, 2014)
In this paper we introduce the concepts of statistical and lacunary statistical convergence of interval numbers in topological groups. We prove some inclusion relations and study some of their properties. Â 